2014
DOI: 10.1504/ijler.2014.062281
|View full text |Cite
|
Sign up to set email alerts
|

A VSM improvement-based approach for lean operations in an Indian manufacturing SME

Abstract: Abstract:The current economic environment in the Indian manufacturing industry is offering a perfect opportunity to SMEs of this country to develop and grow by acting as suppliers of large multinational original equipment manufacturers (OEMs). To meet the challenge of offering high standards of quality, cost and delivery (QCD) to these multinational OEMs, Indian manufacturing SMEs must implement effective approaches, such as lean manufacturing, to continually and systematically improve their operations. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…The results obtained from this pilot test were used to create the future STVSM illustrated in Figure 4. In the traditional VSM approach, the future state map presents a picture of how the system should look after waste and inefficiencies have been eliminated (Addulmalek and Rajgopal, 2007;Saboo et al, 2014). However, in this case the future STVSM also served to validate the improvement strategies implemented during the pilot test stage.…”
Section: Pilot Test and Full Strategy Implementation -Resultsmentioning
confidence: 99%
“…The results obtained from this pilot test were used to create the future STVSM illustrated in Figure 4. In the traditional VSM approach, the future state map presents a picture of how the system should look after waste and inefficiencies have been eliminated (Addulmalek and Rajgopal, 2007;Saboo et al, 2014). However, in this case the future STVSM also served to validate the improvement strategies implemented during the pilot test stage.…”
Section: Pilot Test and Full Strategy Implementation -Resultsmentioning
confidence: 99%
“…Challenges in today's global competition have forced or required manufacturing firms to look for appropriate manufacturing management strategies in order to enhance their efficiency and competitiveness (Lila 2012). To meet the challenge of offering high standards of quality, cost and delivery (QCD) to these multinational OEMs, Indian manufacturing SMEs must implement effective approaches, such as Lean manufacturing, to continually and systematically improve their operations (Saboo et al 2014). To remain competitive in fierce global competition, the Indian automotive component industry needs to have paradigm shift in their thinking to improve its production capabilities, productivity, quality and scalability.…”
Section: Introductionmentioning
confidence: 99%
“…The value stream helps to identify the waste and eliminate it (Kollberg et al, 2006). This step refers to determine the activities and the route of products from start to finish (Saboo et al, 2014), when done correctly will produce product and service that achieve customer value (Othman & Ghaly, 2014). Principle 3-Flow: aims to create a constant flow of product without interruptions from start to finish, such as: avoiding any "bottlenecks" or "Batch and queue" (Sunjka and Murphy, 2014).…”
Section: Lean Management Principlesmentioning
confidence: 99%
“…Principle 3-Flow: aims to create a constant flow of product without interruptions from start to finish, such as: avoiding any "bottlenecks" or "Batch and queue" (Sunjka and Murphy, 2014). Saboo et al (2014) and Othman and Ghaly, (2014) reported that this step required that all effort would be made to reduce the barriers that prevent such flow. Principle 4-Pull: aims to decrease the quantity of material in inventories and applying a "just-intime" (JIT) strategy which means increasing efficiency and decreasing waste by ensuring the flow of the product from the ordering process until it is distributed to the customer (Kollberg et al, 2006).…”
Section: Lean Management Principlesmentioning
confidence: 99%